Colonic Atresia: Association with Other Anomalies - Khaled M. El-Asmar; Mohammed Abdel-Latif; Abdel-Hamid; Mohamed H. Soliman; Mosad M. El-Behery (EL-Med-Pub, 2020)
Background: Colonic atresia (CA) is a rare form of congenital intestinal atresia. Although CA may be isolated, it is more commonly reported in literature in association with other congenital anomalies. Materials and Methods: This study is a review of prospectively collected data of all the patients with colonic atresia presented to our center (Ain Shams University) during 2008 to 2016. Results: Twelve patients were enrolled in this study. The atresia was of type I in one case, type II in four cases, type IIIa in six cases, type IV in one case. These cases accounted for 4.9 % of intestinal atresias managed in our center during the same period. Five cases were isolated CA, while the other seven cases had associated abdominal congenital anomalies (exomphalos, Hirschsprung's disease, imperforate anus, closing gastroschisis, colonic duplication, and multiple small bowel atresia in two cases). The management in ten cases was by staged procedure with creation of a temporary stoma initially, while primary anastomosis was established in two cases. We had two cases with delayed presentations, one missed diagnosis, and three mortalities in this series. Conclusions: The low incidence of CA may result in delay in the diagnosis and management. Hirschsprung's disease should be excluded in every case of colonic atresia. Early diagnosis and proper surgical management is essential for good prognosis.